Overexpression of p53 protein in Barrett's syndrome with malignant transformation. Issue 4 (April 1993) - Fléjou, J F; Potet, F; Muzeau, F; Le Pelletier, F; Fékété, F; Hénin, D
Abstract : AIMS–To study the overexpression of p53 protein in Barrett's oesophagus with adenocarcinoma, and to correlate this expression with the pathological features of Barrett's syndrome. METHODS–Immunohistochemical staining was performed on frozen sections with a monoclonal antibody directed against wild type and mutated p53 protein (Pab 1801). Eleven cases of Barrett's adenocarcinoma were studied, seven of which had extensive sampling of benign Barrett's mucosa. RESULTS–Eight of 11 adenocarcinomas overexpressed the p53 protein. Both early and advanced tumours were positive. In Barrett's mucosa around the p53 positive tumours, high grade dysplasia was positive; low grade dysplasia and non-dysplastic mucosa were negative. CONCLUSIONS–P53 gene mutation with ensuing p53 protein overexpression is a common feature of Barrett's adenocarcinoma, both at early and advanced stages. This mutation appears as a relatively late event during the neoplastic transformation of Barrett's oesophagus.